Actual pseudocapacity for Li ion storage in tunable core‐shell electrode architectures. Issue 5 (28th April 2022) - Xiong, Tuzhi; Gao, Yingxia; Huang, Peng; Huang, Yongchao; Yang, Hao; (Jie Tang) Balogun, M‐Sadeeq
Abstract: Upon evaluating the pseudocapacitance contribution ( k 1 v ) of electrode materials, the exact capacity (also termed as actual pseudocapacity, k Q ) is usually ignored. However, there is a significant variation between k 1 v and k Q . Herein, we designed tunable in situ core‐shell electrode materials to examine the variation between the k 1 v and k Q . Using nickel foam (NF) as the starting material, the internal structure of NF is systematically controlled via in situ strategy to obtain the optimized nickel oxide core–shell architectures (denoted NFNTO). Despite the directly oxidized NF (denoted NFO) exhibits a higher k 1 v (79.1%) than the NFNTO (47.6%), the k Q of NFNTO is ≈2.3 fold larger than NFO at the highest current density of 8.0 mA cm −2 . The higher k Q can be attributed to the integration of titanium that shortens the Li + diffusion pathway, boosts the diffusion co‐efficient and improves the electronic conductivity towards achieving enhanced ionic transport. Abstract : Herein, the significant variation between pseudocapacitive contribution and pseudocapacity of lithium ion batteries (LIBs) is discussed in in situ strategy‐derived three dimensional (3D) tunable in situ core‐shell electrodes. Series of electrochemical performance, kinetics electrochemistry and theoretical analyses is performed that confirms the facile ionic transport kinetics in the in‐situ proposed design.